Level of plasma neuregulin-1 SMDF is reduced in patients with idiopathic Parkinson's disease. (5th February 2015) - Hama, Yuka; Yabe, Ichiro; Wakabayashi, Koichi; Kano, Takahiro; Hirotani, Makoto; Iwakura, Yuriko; Utsumi, Jun; Sasaki, Hidenao
Highlights: We detected and measured NRG1 SMDF protein in plasma. Levels of plasma NRG1 SMDF were correlated with cerebral spinal fluid levels. Levels of plasma NRG1 SMDF were significantly reduced in sporadic PD. Abstract: Parkinson's disease (PD) is characterised by the progressive loss of dopaminergic neurons, neurons that are regulated by the development, protection and function of neuregulin-1 (NRG1)-ErbB4 signals, in the substantia nigra (SN). NRG1 is a neurotrophic differentiation factor and one of its isoforms is a sensory and motor neuron-derived factor (SMDF), mostly expressed in neurons. To examine the relationship between NRG1 SMDF and PD, we tested whether NRG1 SMDF can be detected and measured in plasma and whether their level in plasma correlates with the clinical severity of PD. We detected NRG1 SMDF to be immunoreactive in plasma. Using an ELISA method specific for NRG1 SMDF, we found that NRG1 SMDF levels were significantly reduced in sporadic PD as compared to controls. However, levels of plasma NRG1 SMDF showed no correlation with the clinical severity of PD. Additionally, we found that there was a correlation of NRG1 SMDF levels in CSF with that in plasma where levels in plasma were significantly higher, at approximately ten times that in CSF. Finally, we also examined the expression of NRG1 SMDF in the post-mortem brain using immunohistochemistry and showed that Lewy bodies in the SN of patients with PD were immunoreactive for NRG1 SMDF. In summary, we found that the reduction of plasma NRG1 SMDF is specifically associated with PD, but has no correlation with the clinical severity of PD. These findings of NRG1 SMDF may provide important complementary information for diagnosing the onset of PD.